2009
DOI: 10.2140/jomms.2009.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Corrugation models and the roaring rails enigma: a simple analytical contact mechanics model based on a perturbation of Carter’s solution

Abstract: Corrugation in railways, and especially short pitch corrugation (30-80 mm), is still considered something of an enigma, despite extensive research. Models based on repeated impacts or differential wear, such as Grassie and Johnson's (1985) and Bhaskar et al.'s (1997), seem not to be conclusive, or not to suggest the correct wavelength.Further models have been suggested, either linear (Frederick, Valdivia, Hempelmann, Vassilly and Vincent) or nonlinear (Mueller), but most suggest a constant frequency mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In more recent papers (Afferrante and Ciavarella, 2009a, 2009b, 2010Afferrante et al, 2011aAfferrante et al, , 2011b important advances in the comprehension of the 'enigma' of short-pitch corrugation were done. In particular, it was shown that the short-pitch corrugation can exist at a 'resonance-free' regime (probably due to a sort of a contact resonance and not to any resonance in the system) for rails with continuum supports and at the pinned-pinned resonance regime, as suggested also by Grassie (2009), for rails with discrete supports.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent papers (Afferrante and Ciavarella, 2009a, 2009b, 2010Afferrante et al, 2011aAfferrante et al, , 2011b important advances in the comprehension of the 'enigma' of short-pitch corrugation were done. In particular, it was shown that the short-pitch corrugation can exist at a 'resonance-free' regime (probably due to a sort of a contact resonance and not to any resonance in the system) for rails with continuum supports and at the pinned-pinned resonance regime, as suggested also by Grassie (2009), for rails with discrete supports.…”
Section: Introductionmentioning
confidence: 99%